Isoperformance curves: An application in team selection - Morton, R. H. (Journal of Sports Sciences, 2009)
An isoperformance curve (or surface) defines combinations of two (or more) physiological attributes of individuals such that equal performances for a specified event would be expected of them. Parameters from the two- and three-parameter critical power models are used to illustrate the concept. There are a number of sporting races where teams of individuals compete simultaneously as a unit. Rowing and team pursuit cycling are two well-known examples. Team selection may be difficult if there are more candidates available than places in the team. Based on the assumption that team members should be evenly matched with respect to performance rather than physiological attributes, proximity to a particular isoperformance curve (or surface) may suggest an obvious grouping of individuals. Isoperformance lines also enable identification of an athlete's individual training needs, since the components of the isoperformance lines can be affected by specific training interventions.